Financial contagion in the laboratory: The cross-market rebalancing channel - Cipriani, Marco; Gardenal, Gloria; Guarino, Antonio (Journal of Banking & Finance, 2013)
We present the results of the first experimental study of financial markets contagion. We develop a model of financial contagion amenable to be tested in the laboratory. In the model, contagion happens because of cross-market rebalancing, a channel for transmission of shocks across markets first studied by Kodres and Pritsker (2002). Theory predicts that, because of portfolio rebalancing, a negative shock in one market transmits itself to the others, as investors adjust their portfolio allocations. The theory is supported by the experimental results. The price observed in the laboratory is close to that predicted by theory, and strong contagion effects are observed. The results are robust across different market structures. Moreover, as theory predicts, lower asymmetric information in a (“developed”) financial market increases the contagion effects in (“emerging”) markets.